2020
DOI: 10.18280/mmc_c.811-407
|View full text |Cite
|
Sign up to set email alerts
|

Power Wheelchair Virtual Reality Simulator with Vestibular Feedback

Abstract: Autonomy and the ability to maintain social activities can be challenging for people with disabilities experiencing reduced mobility. In the case of disabilities that impact mobility, power wheelchairs can help such people retain or regain autonomy. Nonetheless, driving a power wheelchair is a complex task that requires a combination of cognitive, visual and visuo-spatial abilities. In practice, people need to pass prior ability tests and driving training before being prescribed a power wheelchair by their the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It has been shown that virtual environment engagement is strongly associated with developing a CS using HMD in standing or sitting subjects [33]. The vestibular system perceives cybersickness as being affected by gaps between virtual and real locations [34][35][36]. While there may be statistically significant differences in the sense of presence for Content-Type, Gender, and Content-Type × gender variables, no statistically significant result may be found for any independent variables related to cybersickness [37].…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that virtual environment engagement is strongly associated with developing a CS using HMD in standing or sitting subjects [33]. The vestibular system perceives cybersickness as being affected by gaps between virtual and real locations [34][35][36]. While there may be statistically significant differences in the sense of presence for Content-Type, Gender, and Content-Type × gender variables, no statistically significant result may be found for any independent variables related to cybersickness [37].…”
Section: Related Workmentioning
confidence: 99%
“…Further evidence by Lai and colleagues also suggested that there were higher frontal-posterior networks during the song condition among children with autism, suggesting a higher level of engagement during musical stimuli. Hence words, sentences and phrases that needed to be learned by students can be written into a song and sung, cultivating their ability to express the written language (Vailland et al, 2020).…”
Section: Literature Review Music Intervention For Children With Autismmentioning
confidence: 99%